State-led funding and support for education innovation programmes: Create a participatory policy to create inclusive and equitable education in Indonesia - Sahl, Dafiq Febriali; Ridho, Afi Ahmad; Putra, Raihan Raidinata (Asian Journal Collaboration of Social Environmental and Education, 2025)
Background: The research focuses on the challenges facing education, particularly the lack of civil society involvement in policy formulation and implementation. Bureaucratic inefficiency, driven by an emphasis on quantity and inertia, hampers educational innovation. The state-funded Education Innovation Programme is designed to address these issues, promoting both educational innovation and the democratisation of education. This programme emphasizes participatory innovation, seeking solutions to the problems within the education system. Methods: This study uses a qualitative approach to analyze the stages of the Education Innovation Programme, including planning, execution, and evaluation. The involvement of innovators, review teams, observers, and government agents is explored in the context of their collaborative, professional, and non-interventionist roles. Findings: The Education Innovation Programme encourages community-driven, innovative ideas with direct state support in terms of funding and mentoring. This collaboration aims to reduce bureaucratic burdens and offer flexible, locally based solutions to education issues. The programme is designed to address the specific problems faced by poor and marginalized groups, enhancing access to education. Conclusion: The Education Innovation Programme has the potential to alleviate access issues in education for marginalized groups, fostering local solutions and empowering civil society. It could provide a more flexible, less rigid approach to solving education problems, particularly in the face of bureaucratic limitations. Novelty/Originality of this Study: This study offers a novel perspective on addressing educational challenges by advocating for a collaborative, bottom-up approach through the Education Innovation Programme. It highlights the potential of state-backed, community-driven innovation to overcome bureaucratic inertia and improve access to education for marginalized communities.